2021
DOI: 10.1002/capr.12407
|View full text |Cite
|
Sign up to set email alerts
|

What metrics of harm are being captured in clinical trials involving talking treatments for young people? A systematic review of registered studies on the ISRCTN

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 42 publications
(55 reference statements)
0
4
0
Order By: Relevance
“…Our findings indicate that TM is a relatively well-tolerated and feasible intervention for survivors of domestic violence, with participants reporting few adverse events, most of which were mild and transient in nature. While worsening of symptoms and/or the manifestation of psychosomatic adverse effects are not uncommon with psychological and meditative therapies (Muschalla et al, 2020;Schermuly-Haupt et al, 2018;Taylor et al, 2022), reporting of adverse events to psychological therapies (including TM) is largely inadequate (Condon et al, 2021;Hayes & Za'ba, 2022). The few clinical studies that have purposefully measured adverse events to TM (Leach et al, 2015) have similarly reported psychosomatic adverse events to TM, though the intensity and frequency of events reported in our study was relatively lower.…”
Section: Discussionmentioning
confidence: 58%
“…Our findings indicate that TM is a relatively well-tolerated and feasible intervention for survivors of domestic violence, with participants reporting few adverse events, most of which were mild and transient in nature. While worsening of symptoms and/or the manifestation of psychosomatic adverse effects are not uncommon with psychological and meditative therapies (Muschalla et al, 2020;Schermuly-Haupt et al, 2018;Taylor et al, 2022), reporting of adverse events to psychological therapies (including TM) is largely inadequate (Condon et al, 2021;Hayes & Za'ba, 2022). The few clinical studies that have purposefully measured adverse events to TM (Leach et al, 2015) have similarly reported psychosomatic adverse events to TM, though the intensity and frequency of events reported in our study was relatively lower.…”
Section: Discussionmentioning
confidence: 58%
“…In time, all studies assessing school-based mental health interventions should measure and report cases of symptom deterioration and other adverse effects as standard, as happens with clinical trials. 9 More importantly, it should become standard to have a plan of what to do with adolescents who deteriorate during these interventions – for example, to conduct follow-up assessments and offer group or individual interventions as necessary. When there is an evidence base demonstrating which individuals are more likely to experience harm from school interventions, then more tailored, effective support can be offered.…”
Section: Discussionmentioning
confidence: 99%
“…It has long been recognised that the psychological therapies on which interventions are based can cause harm in a minority of individuals, including adolescents. 8 , 9 There is also an established body of literature demonstrating harms from public health interventions. 4 As school-based mental health interventions similarly aim to change adolescents’ thoughts, feelings or behaviours, it is reasonable that this too might have negative effects for some individuals.…”
Section: The Problem With School Mental Health Interventionsmentioning
confidence: 99%
“…Despite CBT’s historical promotion as the ‘gold standard’, a growing body of literature is critical of this perspective. This literature argues that claims about CBT’s superiority lack thorough assessment and fail to acknowledge potential harms or iatrogenic effects (Castro Batic and Hayes, 2020; Hayes and Za’ba, 2021; Lilienfeld, 2007; Parry et al., 2016). In addition, there is increasing evidence that CBT may not be the most suitable approach and can even be potentially harmful for certain marginalized communities, such as autistic individuals (Babb et al., 2022), who are overrepresented in eating disorder populations (Huke et al., 2013).…”
Section: Introductionmentioning
confidence: 99%